Tren Penelitian Media Digital STEM pada Pembelajaran IPA SMP di Indonesia: Systematic Literature Review 2014-2024 - Rizki Nor Amelia; Rohanah Rohanah (Program Studi Pendidikan IPA, FKIP Universitas Pancasakti (UPS) Tegal, 2026)
In this era of technological development, innovation in learning has become an urgent need, one of which is through the use of digital media. This study aims to analyze the use of STEM-based digital media among junior high school students in Indonesia between 2014 and 2024. The method used is a Systematic Literature Review (SLR) by analyzing 54 articles from national and international journals. The results of the analysis show that the dominant research method is quantitative with a quasi-experimental design (92%), with the most publications in 2023 (43%). The most widely used type of digital media is e-modules (28%), while the data collection technique generally uses a mixed method (61%). Descriptive data analysis dominated (91%), with critical thinking skills as the most frequently studied dependent variable (15%), and science subjects as the most common context (56%). These findings provide insights for educators, researchers, and developers to optimize the implementation of STEM-based digital media in the learning process.